2020
DOI: 10.2147/jpr.s230394
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychological Characteristics in Patients with Chronic Complex Regional Pain Syndrome: Comparisons with Patients with Major Depressive Disorder and Other Types of Chronic Pain</p>

Abstract: Objective: This study investigated psychological characteristics of patients with chronic complex regional pain syndrome (CRPS) and examined relationships between psychosocial factors and pain severity. Methods: In total, 76 patients with CRPS, 95 patients with other types of chronic pain, 171 healthy controls, and 66 patients with major depressive disorder (MDD) were included. Minnesota Multiphasic Personality Inventory (MMPI-2) profiles and scores on the Beck Depression Inventory and State-Trait Anxiety Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…This finding is in line with a study conducted by Park et al, who found that patients with chronic CRPS were not more psychologically disturbed than other chronic pain patients. 43 Our study confirms the utility of the INTERMED to identify complex patients, including those in this population, and to direct interdisciplinary care.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is in line with a study conducted by Park et al, who found that patients with chronic CRPS were not more psychologically disturbed than other chronic pain patients. 43 Our study confirms the utility of the INTERMED to identify complex patients, including those in this population, and to direct interdisciplinary care.…”
Section: Discussionsupporting
confidence: 80%
“…The results of studies concerning the role of psychological factors in the development of CRPS are inconclusive. More dated studies have suggested the association does not exist; however, more recent studies have suggested that there is a connection between psychological factors and pain outcomes in patients with CRPS [ 48 ]. Few studies have been conducted on this topic and for us to truly under the relationship more research is needed.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…A chronic state of illness or pain is often associated with reactive depression and anxiety as well as higher scores on many of the MMPI subscales [ 25 , 26 ]. Additionally, among adolescents and children with CRPS, the risks of somatization, anxiety, and depression are high, and the duration of pain and depression has been shown to be associated with suicidal ideation [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%